A SWOT analysis of pre-primary program in slums of Dhaka city run by Surovi (NGO). - Alam, Md. Farhad (BRAC University, 2012)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Science in Early Child Development, 2011.